Epidemiological study of lymphedema prevalence and comorbidities in hospitalized patients in the United States - Gérard, Nicolas; Farmakis, Ioannis T.; Valerio, Luca; Hobohm, Lukas; Keller, Karsten; Kucher, Nils; Barco, Stefano; Grigorean, Alexandru (Journal of Clinical Medicine, 2025)
Background/Objective: Lymphedema is a disabling condition that is both underdiagnosed and undertreated. Epidemiological data on this disease is sparse. Methods: The prevalence of lymphedema was studied in hospitalized patients registered in the Nationwide Inpatient Sample (NIS) of the United States (US) from 2016 to 2020. ICD-10 codes related to lymphedema were utilized to identify eligible cases. We studied comorbidity burden and outcomes during hospitalizations, including in-hospital fatality, length of stay and total charges per hospitalization. Results: Lymphedema was present in 0.45% (n = 792,475) of all hospitalizations; with prevalence increasing from 0.40% in 2016 to 0.50% in 2020. Lymphedema-mentioning hospitalizations peaked in July. The median age was 67 (IQR: 57-77) years; A total of 60% were female. Most lymphedema-mentioning hospitalizations were emergency admissions (90%). The most frequent comorbidities were arterial hypertension (77%), obesity (58%), diabetes mellitus (42%), phlegmon (38%), renal disease (32%), chronic pulmonary disease (31%), and cancer (26%). The in-hospital fatality rate was 2.3%, the median length of stay was 5 (IQR: 3-8) days, and each hospitalization incurred a median of 36,304 (IQR: 20,431, 67,171) US dollars, roughly three times higher than the average hospitalization costs in the NIS in the same period. Conclusions: This represents the first comprehensive nationwide study of the epidemiological and economic burden of lymphedema among hospitalized patients in the US. The findings highlight that lymphedema, although underdiagnosed, affects a significant number of patients and is associated with a considerable burden of both comorbidities and costs.